Bailout with white revolution or sink deeper?: groundwater depletion and impacts in the Moga District of Punjab, India - Amarasinghe, Upali A.; Smakhtin, Vladimir U.; Sharma, Bharat R.; Eriyagama, Nishadi (International Water Management Institute, 2010)
Moga District in Punjab, India, is a microcosm of the twin story of irrigation-induced growth and stress. The groundwater consumptive water use in agriculture exceeds the recharge by a substantial margin. Rice production contributes to a major part of this difference. The groundwater depletion is so critical that diversifying agriculture is the only way forward for sustainable agricultural growth. Reducing the rice area and intensifying milk production will be a win-win situation for both the farmers and the area reeling with a groundwater crisis.